Consolidation anti-CD22 fractionated radioimmunotherapy with 90Y-epratuzumab tetraxetan following R-CHOP in elderly patients with diffuse large B-cell lymphoma: a prospective, single group, phase 2 trial. Issue 1 (January 2017) - Kraeber-Bodere, Françoise; Pallardy, Amandine; Maisonneuve, Hervé; Campion, Loïc; Moreau, Anne; Soubeyran, Isabelle; Le Gouill, Steven; Tournilhac, Olivier; Daguindau, Etienne; Jardel, Henry; Morineau, Nadine; Bouabdallah, Krimo; et al.
Summary: Background: Radioimmunotherapy represents a potential option as consolidation after chemoimmunotherapy in patients with diffuse large B-cell lymphoma who are not candidates for transplantation. We aimed to assess activity and toxicity of fractionated radioimmunotherapy using anti-CD22 90 Y-epratuzumab tetraxetan as consolidation after front-line induction chemoimmunotherapy in untreated elderly patients with diffuse large B-cell lymphoma. Methods: We did a prospective, single-group, phase 2 trial at 28 hospitals in France, with patients recruited from 17 hospitals. Eligible patients were aged 60–80 years with bulky stage 2–3 or stage 3–4 CD20-positive diffuse large B-cell lymphoma, previously untreated, and not eligible for transplantation. Patients received six cycles of R-CHOP (rituximab [375 mg/m 2 ], cyclophosphamide [750 mg/m 2 ], doxorubicin [50 mg/m 2 ], and vincristine [1·4 mg/m 2, up to 2 mg] all on day 1, and prednisone [40 mg/m 2 ] daily for 5 days), administered every 14 days. 6–8 weeks after R-CHOP, responders received two doses of 15 mCi/m 2 (555 MBq/m 2 ) 90 Y-epratuzumab tetraxetan administered 1 week apart. The primary endpoint was 2 year event-free survival in all registered eligible patients who received at least 1 day of study treatment; the safety analysis was done in the same population. This trial is registered withClinicalTrials.gov, numberNCT00906841 . Findings: Between Oct 22, 2008, and Dec 16, 2010, we recruited 75 patients, of whom four (5%) were excluded after central pathology review; hence, 71 (95%) patients were included in the analysis. All patients started induction treatment; 57 (80%) received radioimmunotherapy. With a median follow-up of 37 months (IQR 30–44), the estimated 2 year event-free survival was 75% (95% CI 63–84). Radioimmunotherapy toxicity consisted of grade 3–4 thrombocytopenia in 48 (84%) of 57 patients and neutropenia in 45 (79%) of 57 patients. One patient developed myelodysplastic syndrome 28 months after receiving radioimmunotherapy and one patient developed acute myeloid leukaemia 5 months after receiving radioimmunotherapy. Interpretation: Fractionated radioimmunotherapy with 90 Y-epratuzumab tetraxetan might be appropriate for response consolidation after induction chemotherapy in older patients with advanced diffuse large B-cell lymphoma, but further comparative studies are needed. Funding: Immunomedics, Amgen, Canceropôle Grand Ouest, the GOELAMS/LYSA group and the French National Agency for Research (Investissements d'Avenir).